The development of computerised accounting system in goods and services tax in Malaysia: client and vendor perspectives / Nor Hafizah Abd Mansor - Abd Mansor, Nor Hafizah (2022)
This study focuses on the goods and services tax (GST) technological aspect, namely GST-compliant computerised accounting system. The study aims to explore the development of GST-compliant computerised accounting system throughout the GST phases: pre-GST implementation, GST implementation, and post-GST implementation from the client and vendor perspectives. The presence of GST-compliant computerised accounting system is needed to facilitate the implementation of GST. GST-compliant computerised accounting system is defined as accounting software capable of recording, processing economic data, storing financial information, and generating reports embedded with eight GST attributes determined by the tax authority. However, developing a computerised accounting system to GST-compliant is challenging and multidimensional, involving unique phases, processes, activities, issues, and people. Hence, the current study attempts to seek qualitative evidences that would explain how the GST-compliant computerised accounting system is developed from the client and vendor perspectives throughout the GST phases. Besides, the study is intended to identify the socio and technical issues influence the development of GST-compliant computerised accounting system. In order to promote better understanding on the phenomenon and to strengthen findings under the study, tax authority’s experience is considered. Also, considering several key gaps found in previous studies, this study employed a triangulation of theories; Stakeholder Theory and Stakeholder Salience Theory, System Development Life Cycle (SDLC), and the Socio Technical System Theory (STST) as a lens to explore the development of GST-compliant computerised accounting system. The current study used interpretivism ontology to explore the issue in conjunction with the research issue highlighted and supported in the literature. Accordingly, three case studies were selected to explore, describe, and explain deep insights about the phenomenon under study from the client (business), vendor (system developer) and tax authority’s perspectives, which most prior studies have neglected. Furthermore, this interpretive case study allowed the researcher to interpret meaningful experiences from the client, vendor, and tax authority for theory building (inductive). Regarding the data analysis aspect, data transcribing, data coding, and thematic coding were the main elements of this interpretive qualitative case study. Moreover, three individual case studies, namely, client, vendor, and the tax authority’s cross-case analyses were conducted for further discussion. In developing the GST-compliant computerised accounting system, both client and vendor, as well as tax authority, encountered various processes, activities, socio, and technical issues for each GST phase. Importantly, GST mapping (designing process) during pre-GST implementation is a critical system development activity from both client and vendor perspectives. Cross-case analyses managed to identify socio and technical issues from client and vendor perspectives, as well as client, vendor, and tax authority perspectives throughout the GST phases. Overall, people (socio) and technology (technical) were the main influencing factors to the development of GST-compliant computerised accounting system. The proposed conceptual framework redirects findings from the qualitative nature of current study, in which the development of GST-computerised accounting system involves distinct processes, activities, socio, and technical issues throughout the GST phases.